PENGARUH PERTUMBUHAN PERUSAHAAN, PROFITABILITAS, LIKUIDITAS, DAN STRUKTUR AKTIVA TERHADAP LEVERAGE KEUANGAN PERUSAHAAN SUBSECTOR TEXTILE AND GARMENT DI BEI - Siregar, Dewi Rosita Hafsari; Wiksuana, I Gusti Bagus (E-Jurnal Manajemen, 2015)
Debt as external financial source could act as leverage for earning per share (EPS) of company. The purpose of this study is to understand the influence of company’s growth, profitability, liquidity, and tangibility of asset to financial leverage of companies that listed in subsector textile and garment in BEI for period 2006-2013, after the abolition of quotas and the reduction of tariff duties among the contracting nations based on General Agreement on Tariffs and Trade (GATT). The population and also as the total sample in this study is 11 companies. Technical analysis using SPSS multiple analysis regression programe. The results shows that profitability has negative significant influence to financial leverage and tangibility of asset has positif significant influence to financial leverage of subsector textile and garment companies. Meanwhile, company’s growth and liquidity has no significant influence to financial leverage of subsector textile and garment companies. Keywords: company’s growth, profitability, liquidity, tangibility of asset, financial leverage
Keywords: company’s growth, profitability, liquidity, tangibility of asset, financial leverage